عقد الوكالة في الفقه الإسلامي وعلاقته بشركات التأمين في ماليزيا - Mohd Faiz bin Zainul Abidin (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2009)
The aim of this study to examine wakalah (authorization) in Islamic Jurisprudence by emphasizing the wisdom behind its legislation as well as the basis, the conditions, the types and other matters asscociated with authorization in the Islamic Jurisprudence. In addition, this study discusses the experiences of the Islamic Insurance companies in Malaysia that used the concept of authorization in managing and marketing it's products. Some issues associated with the agencies are also considered such as the worker's allowance and administrative expenses. The different opinions of Islamic scholars and expert in the field of Economics were also consulted. The researcher come up with the important results related to the agency, such as the equalization in the application of the agency concept among the Islamic Insurance companies and the conventional insurance companies.